Selective scene perception deficits in a case of topographical disorientation. (July 2017) - Robin, Jessica; Lowe, Matthew X.; Pishdadian, Sara; Rivest, Josée; Cant, Jonathan S.; Moscovitch, Morris
Abstract: Topographical disorientation (TD) is a neuropsychological condition characterized by an inability to find one's way, even in familiar environments. One common contributing cause of TD is landmark agnosia, a visual recognition impairment specific to scenes and landmarks. Although many cases of TD with landmark agnosia have been documented, little is known about the perceptual mechanisms which lead to selective deficits in recognizing scenes. In the present study, we test LH, a man who exhibits TD and landmark agnosia, on measures of scene perception that require selectively attending to either the configural or surface properties of a scene. Compared to healthy controls, LH demonstrates perceptual impairments when attending to the configuration of a scene, but not when attending to its surface properties, such as the pattern of the walls or whether the ground is sand or grass. In contrast, when focusing on objects instead of scenes, LH demonstrates intact perception of both geometric and surface properties. This study demonstrates that in a case of TD and landmark agnosia, the perceptual impairments are selective to the layout of scenes, providing insight into the mechanism of landmark agnosia and scene-selective perceptual processes.